2005
DOI: 10.1116/1.1849220
|View full text |Cite
|
Sign up to set email alerts
|

Cleaning of extreme ultraviolet lithography optics and masks using 13.5nm and 172nm radiation

Abstract: Articles you may be interested inFocused helium and neon ion beam induced etching for advanced extreme ultraviolet lithography mask repair

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…These deposits were imaged and quantified by AFM and STXM (Fig. 7,15,18,19 The fluence involved in collecting single images for OD measurements was 0.5 6 0.1 mJ/cm 2 . The rate of deposition observed was directly proportional to fluence (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These deposits were imaged and quantified by AFM and STXM (Fig. 7,15,18,19 The fluence involved in collecting single images for OD measurements was 0.5 6 0.1 mJ/cm 2 . The rate of deposition observed was directly proportional to fluence (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…), and become fixed to surfaces as a carbonaceous layer when irradiated with ionizing radiation. 2,5,8,11,12,[15][16][17] The results are sometimes mixed, 8,9,12 but in certain cases the reflectance can be fully recovered, 15 and an optic can survive multiple cleaning cycles. The carbonaceous deposits are often highly undesirable as they can degrade the transmissive or reflective properties of optics, introduce spectroscopic artifacts, and/or decrease the efficiency of detectors.…”
Section: Introductionmentioning
confidence: 99%
“…These results are in agreement from previous Augerelectron spectroscopy experiments [50] where both Ca + and F À ions were strongly bonded to Si sites. Possible formation of Li trimmers and bonding of Li and Si atoms can be indirectly verified from the in-homogeneity of concentration of Si and F atomic species [36].…”
Section: Resultsmentioning
confidence: 99%
“…Considering the dependence on the type of contaminant, it was found that hydrocarbon ions, water ions, alkali metal ions can be removed after multiple irradiation of optical surface at 157 nm with trace levels of oxygen in the purge gas [33][34][35]. In certain cases, the films of molecular contaminants formed on optical surfaces can be removed by cleaning them with appropriate solvents or by applying several cleaning techniques such as CO 2 snow cleaning, ion or laser cleaning, on-orbit exposure to ambient atomic oxygen, synchrotron radiation heating and VUV irradiation [36]. Exposure of contaminated surfaces at longer wavelengths is less efficient to clean due to lower photon energy and lower fragmentation probability than exposure at short wavelengths [37,38].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the cleaning processes that remove contamination and restore the photomask pattern are one of the most important portions of semiconductor fabrication. [7][8][9][10][11][12] Current processes for cleaning EUV lithography reflectors involve many corrosive and oxidizing environments, including acids, bases, UV/ozone, and plasma. 5,6,[13][14][15][16][17][18] However, cleaning processes that involve corrosive chemicals cause surface oxidation of the Ru capping layers, 19 resulting in surface corrosion and deterioration of the EUV reflector.…”
Section: Introductionmentioning
confidence: 99%